The book of JavaScript : a practical guide to interactive Web pages - Thau (No Starch Press, 2006)
The Book of JavaScript teaches readers how to add interactivity, animation, and other tricks to their websites with JavaScript. Rather than provide a series of cut-and-paste scripts, thau! takes the reader through a series of real world JavaScript code examples with an emphasis on understanding. Each chapter focuses on a few important JavaScript features, shows how professional websites incorporate them, and shows readers how they might add those features to their own websites. This thoroughly updated 2nd edition includes coverage of Ajax, revised appendices, and new examples throughout. Summa.